Mapping drought patterns and impacts: a global perspective - Eriyagama, Nishadi; Smakhtin, Vladimir U.; Gamage, M.S.D.Nilantha (International Water Management Institute, 2009)
The study examines the global pattern and impacts of droughts through mapping several drought-related characteristics - either at a country level or at regular grid scales. It appears that arid and semi-arid areas also tend to have a higher probability of drought occurrence. It is illustrated that the African continent is lagging behind the rest of the world on many indicators related to drought-preparedness and that agricultural economies, overall, are much more vulnerable to adverse societal impacts of meteorological droughts. The study also examines the ability of various countries to satisfy their water needs during droughts using storage-related indices.